2013
DOI: 10.1159/000353346
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Foreign-Body Granuloma of the Glabella due to Polyacrylamide Filler and an Intractable Ulcer after Skin Biopsy: An Immunohistochemical Evaluation of Inflammatory Changes

Abstract: Introduction: Polyacrylamide hydrogel has been considered a safe and biocompatible soft tissue filler, and it has been widely used in cosmetic procedures. However, recent studies have revealed some complications with polyacrylamide filler injections. Case Report: We present the case of foreign-body granulomas of the glabella, which subsequently formed an infectious ulcer 3 years after a polyacrylamide injection. An immunohistochemical evaluation of the foreign-body granulomas was performed in order to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Therefore, despite the polyacrylamide hydrogel is not a complement activator it caused obvious FBR after implantation. Our observation is consistent to other researchers’ reports on the foreign-body granuloma of the glabella due to polyacrylamide filler 50 .…”
Section: Resultssupporting
confidence: 94%
“…Therefore, despite the polyacrylamide hydrogel is not a complement activator it caused obvious FBR after implantation. Our observation is consistent to other researchers’ reports on the foreign-body granuloma of the glabella due to polyacrylamide filler 50 .…”
Section: Resultssupporting
confidence: 94%
“…PAAG injections can cause short-term and long-term adverse reactions. Studies have shown that long-term implantation of PAAG for augmentation mammaplasty elicited foreign-body chronic inflammation and granulomatous reactions ( 7 , 9 , 10 ). Foreign-body granuloma formation and inflammatory cell infiltration are the characteristic histopathological features after cosmetic augmentation mammaplasty with an injection of PAAG.…”
Section: Discussionmentioning
confidence: 99%
“…Like PTFE and silicone, polyacrylate-polyalcohol copolymer and polyacrylamide hydrogel are non-biodegradable, meaning they can remain within the body permanently. They both have a favorable histopathologic profile, but foreign-body reactions are possible (117)(118)(119)(120). Polyacrylate-polyalcohol copolymer has been associated with risks of periureteral fibrosis (potentially complicating subsequent ureteral reimplantation) and obstruction of the vesicoureteral junction (116,121).…”
Section: Endoscopic Injectionmentioning
confidence: 99%